REPRESENTASI NILAI MOTIVASI PADA BUKU "I HATE DIET" KARYA YULIA BALTSCHUN - Nur Abidah, Amelia; Firmonasari, Aprillia (MIMESIS, 2022)
Verbal language is vital in communication and is the most important means of interaction. By the significant role of verbal language, visuals are often less considered unnecessary, even though they could help to understand communication better. Verbal and visual language are interconnected and simultaneously build a strong, complete, structured text. This research focused on how a book writer communicates using two or more modes simultaneously, namely text and images, which is called multimodal discourse analysis, particularly social semiotics. This study analyzes the illustrated book "I Hate Diet" by Yulia Baltschun. Using a descriptive qualitative method that refers to the theory of reading images, Kress & Leeuwen's (2006) analysis relates to the existence of representational and interactive meanings with images divided into three aspects: information value, salience, and framing. In connection with the data analysis in the form of text or verbal, it is analyzed using the theory of seven development tasks by Gee (2011). The results indicated the meanings of the image or visual illustrations supported by verbal or text analysis. There are several representations of meaning in it, namely the meaning of motivational invitations and warnings or meanings that remind.